Phonology and Maharah Kalam in Scopus Publications: Content Analysis and Development Trends - Ardianingtyas, Nurani Tri; Nurrohman, Taufik (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
This study explores the relationship between phonology and Arabic language learning by analyzing document publications indexed in Scopus from 1980 to 2022. Focusing on maharah kalam (speaking skills) phonology, this study investigates its integration into Arabic education, the prominent affiliations, and researchers' search approaches. Using bibliometric analysis, the findings reveal an irregular annual publication pattern, mostly articles (181 document articles). The University of Haifa leads with 19 articles, and Amayreh MM. is the most prolific author (five articles). Sub-content trends vary over the decade. Recommendations include increased publications, exploring the University of Haifa's role, and encouraging Indonesian researchers. The study concludes with future research avenues, emphasizing expanded publications and exploring the University of Haifa's impact. In summary, it provides insights into phonology and maharah kalam studies, identifies contributors, and suggests future directions within Scopus publications from 1980 to 2022.